2015
DOI: 10.1007/s00535-014-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for management of colorectal polyps

Abstract: Background Recently in Japan, the morbidity of colorectal polyp has been increasing. As a result, a large number of cases of colorectal polyps that are diagnosed and treated using colonoscopy has now increased, and clinical guidelines are needed for endoscopic management and surveillance after treatment. Methods Three committees [the professional committee for making clinical questions (CQs) and statements by Japanese specialists, the expert panelist committee for rating statements by the modified Delphi metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(148 citation statements)
references
References 59 publications
2
145
0
1
Order By: Relevance
“…There is no mention in the Japanese Colorectal Polyp guidelines [21] about CP, but it is stated in the guidelines that conventional polypectomy for polyps <5 mm in size involves more risk than benefit. We think this trend should be changed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There is no mention in the Japanese Colorectal Polyp guidelines [21] about CP, but it is stated in the guidelines that conventional polypectomy for polyps <5 mm in size involves more risk than benefit. We think this trend should be changed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective large study involving 2053 subjects of first screening colonoscopies showed a strong direct correlation between WT and all adenoma detection rate (r = 0.90) [8] and a study using multivariate analysis indicated that the endoscopist was more powerful on adenoma detection than the well-established predictions of advancing age or male gender [10]. The Japanese guidelines recommend that diminutive adenomas ≤ 5 mm should be followed up in the absence of colonoscopic findings suggestive of carcinoma [11]. Most of diminutive polyps including adenoma are characterized at real-time using narrow-band imaging, and are not necessarily removed nor diagnosed by pathological examination in the clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research, as a next step, is necessary to establish optimal surveillance strategies and time-intervals. On the other hand, it is [55] 1e2 adenomas <10 mm Intermediate 3e4 adenomas Any 10 mm High 5 adenomas 3 adenomas with at least one 10 mm Japan Society of Gastroenterology [72] 5 mm 5 mm Cancer Council Australia [73] 1e2 adenomas <10 mm 3 adenomas Any 10 mm HGD Villous component a It is optional to consider these risk factors or not. possible that in future, other factors like molecular markers detected in polyps, blood or stool might provide information about an individual's risk to develop metachronous advanced neoplasia, going beyond size and number of polyps as main indicators for surveillance colonoscopies.…”
Section: Low-risk Adenoma Patientsmentioning
confidence: 99%